Implementasi Kebijakan Peraturan Menteri Kesehatan RI Nomor 21 Tahun 2013 Tentang Penanggulangan HIV/AIDS di Kota Bontang - Gaspersz, Angel Azalia Caroline; Amin, Muhammmad Jamal; Rande, Santi (Jurnal Ilmu Pemerintahan, 2021)
The purpose of this study was to identify the factors that influence the implementation of government policies in eradicating infectious diseases (HIV-AIDS) in the city of Bontang. The basic analysis used in this study is qualitative, which produces descriptive information. The type of analysis used is descriptive analysis which aims to produce a transparent picture of the implementation of the duties and functions of the KPA in eradicating HIV/AIDS in Bontang City. Information was collected through recordings, interviews, coordinate perception, participatory perception and the physical environment. In addition, the information obtained is simplified to be unique, especially efforts to encapsulate bits, shapes, and information. Another preparation is drawing conclusions and confirming after the information presented in expressive frames and coherent clarification has been captured. The emergence of this thought shows that there is potential for human resources in the Bontang City Government Office. However, in carrying out the obligations and capacities of the KPA, communication between organizations has not been ideal, resulting in wasteful organizational communication, inadequate working conditions and often poor work execution. The working capacity of development planning that has not been maximized needs to be managed carefully so that it does not become a threat to the eradication of HIV/AIDS in Bontang City. The communication factor between non-independent institutions and the bureaucracy actually greatly influenced the AIDS response process in Bontang City. Therefore, the organization formulated a plan to make KPA an independent organization and no longer subject to the City Government of Bontang.